POTENTIAL OF COLI FRUIT AS ANIMAL FEED IN MOA DISTRICT SOUTHWEST MALUKU - Peassy, Ferderika; Eoh, Marno; Aponno, Hendrik (RUMPHIUS, 2023)
This study aims to determine the distribution area and population of Koli trees on Moa Island and to determine the amount of fruit and mesocarp juice in one production. This research used a survey method, simple random interviews of 30 respondents and direct observation at the research location. Research variables: Respondent profile: age, gender, education level and occupation. Coli tree population structure. Calculating the production of cauliflower and mesocarp fluid. The results of the study: Respondents' age was 23-64 years old, male sex (100%), education level of respondents: Elementary school graduates (SD) 70%, respondent's main occupation: farmer 93.33%, sideline: breeder 80.00%. Koli tree production area/sample village: 16,000m2/1.6Ha consisting of 4 lanes, area of each lane 4,000m2/0.4Ha, consisting of 4 plots, area of each plot: 1,000 m2/0.1Ha, number of coli trees per plot : 8 trees, number of koli trees in the production land area/village: 8×4×4=128 trees. Coli fruit production for 1 harvest is 20 bunches × 20 fruit = 400 fruit/tree, multiplied by the number of koli trees from one village: 400×128 = 51,200 fruit harvested 2/year: 51,200×2 = 102,400 fruit/village/year, liquid mesocarp/fruit: 260grams and 446grams. Mesocarp fluid/village: 446 gram×102,400 fruit = 45,670,400 gram/45,670.4 Kg/45.7 Ton (large fruit), 260 gram×102,400 fruit = 26,624,000 gram/26,624 Kg/26.62 Ton (small fruit). 1 year mesocarp fluid production in 3 sample villages is 79.86-137 tons/year.